2020
DOI: 10.14309/ajg.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Bedside Predictors of the First Episode of Overt Hepatic Encephalopathy in Patients With Cirrhosis

Abstract: INTRODUCTION: Hepatic encephalopathy (HE) is associated with marked increases in morbidity and mortality for patients with cirrhosis. We aimed to determine the risk of and predictors for HE in contemporary patients. METHODS: We prospectively enrolled 294 subjects with Child A-B (70% Child A) cirrhosis and portal hypertension without previous HE from July 2016 to August 2018. The primary outcome was the development of overt HE (grade >2). We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…Risk factors for MHE in our study were use of diuretics and decompensated cirrhosis, as previously described 21 , 22 , suggesting that our population was appropriate to evaluate response to rifaximin.…”
Section: Discussionsupporting
confidence: 65%
“…Risk factors for MHE in our study were use of diuretics and decompensated cirrhosis, as previously described 21 , 22 , suggesting that our population was appropriate to evaluate response to rifaximin.…”
Section: Discussionsupporting
confidence: 65%
“…Hepatic encephalopathy is a neurological disorder related to the severe decline of liver function. Tapper et al (5) found that 21% of cirrhotic patients with Child-Pugh grade A and B liver function developed hepatic encephalopathy within 1 year. The research of Cordoba et al (6) showed that the mortality of patients with chronic and acute liver failure complicated with hepatic encephalopathy was significantly higher than that of patients without hepatic encephalopathy, which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study proposes a new neuroimaging biomarker for the detection of MHE. As we know, MHE has the potential to progress into OHE, which can cause irreversible brain damage (Tapper et al, 2020). Studies have shown that MHE can be reversed by prompt treatment (Abid et al, 2020;Butterworth & McPhail, 2019;Nardone et al, 2016); therefore, it is important to diagnose and treat MHE before major neurological damage occurs.…”
Section: Discussionmentioning
confidence: 99%